TINJAUAN DESAIN VISUAL BOARDGAME WAROONG WARS Edisi II - Alfons Christian Hardjana (Universitas Katolik Soegijapranata, Semarang, 2021)
Waroong Wars is a board game from Indonesia that can introduce Surabaya signature dishes to the people of Indonesia and abroad. The first printing was published in 2015. Waroong War underwent developments in 2018 resulting in a second printing edition which has a much different visual from the first printing edition. This study will analyze the visual style in the second edition of Waroong Wars which is heavily influenced by the realist style to assess the design. This study uses a descriptive qualitative method with the analysis process using a design critique and is supported by boardgame theory and visual elements. Waroong Wars is an informative, persuasive, and creative board game. Unfortunately, there is no consistency of illustration style that is close to the local flavor. On the other hand, this second edition of Waroong Wars is an interesting strategy to introduce Surabaya's local culinary specialties through the board game and can be applied to other foods.